Pelatihan Pemanfaatan Ai Dalam Pembuatan Konten Kreatif Di SMPN 17 Kota Bengkulu - Yansyah, Novi; Savela, Yela; Widiatama, Danang; Octaviani, Vethy; Maryaningsih, Maryaningsih; Narti, Sri (LPPM Universitas Dehasen Bengkulu, 2025)
The use of artificial intelligence (AI) in education, especially in improving student creativity, is the focus of this study. The training provided to students of SMPN 17 Kota Bengkulu showed that AI can be an effective tool to support creative learning processes. However, this training also identified a digital divide among students, especially related to the use of email. The results of this training provide important implications for the development of educational curricula that integrate AI technology and improve students' digital literacy. This training is also useful for exploring the potential of artificial intelligence (AI) in improving the creativity of students of SMPN 17 Kota Bengkulu. Through training that focuses on tools such as Bing, Suno, and Remaker, students are trained to produce various types of creative content. The results of the training show that students are enthusiastic and able to utilize the artificial intelligence program. In the training, obstacles were found, namely the lack of student understanding regarding the use of email as an account to access AI applications. This training concluded that the importance of integrating AI learning in schools and the need to improve students' digital literacy.